2019
DOI: 10.3390/agriculture9070152
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Distribution of Soil Trace Elements around Kitchener Drain in the Northern Nile Delta, Egypt

Abstract: The pollution of agricultural soils, water and plants by trace elements (TEs) in the Nile Delta Region, Egypt, is of great importance. This study aimed to investigate the spatial and seasonal variation of some TEs in the agricultural area adjacent to Kitchener Drain and to evaluate the ecological risk posed by these elements using six indices. Soil and plant samples were collected from seven sites close to the drain, while water samples were collected from the corresponding sites inside the drain during three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 63 publications
6
22
5
Order By: Relevance
“…The investigated drains contained a higher level of Cd, but lower levels of Ni and Pb, than other drains of the Nile Delta, such as the Kitchener drain that had 4.10 mg kg −1 of Cd, 68.7 mg kg −1 of Ni, and 83.4 mg kg −1 of Pb [ 9 ]. Furthermore, the data of this study indicated that the mean values of the estimated heavy metals were lower than that reported by [ 40 ] for three drains (Elhoks, El-Shakhlouba and Drain 7), [ 45 ] for the Kitchener Drain, and [ 47 ] for contaminated wetlands in Egypt. In addition, Eid et al [ 48 ] recorded 11.9–12.6 mg kg −1 of Ni and 12.7–13.7 mg kg −1 of Pb in the sediment of Burullus Lake of Egypt, which tended to be lower than that estimated in this study.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The investigated drains contained a higher level of Cd, but lower levels of Ni and Pb, than other drains of the Nile Delta, such as the Kitchener drain that had 4.10 mg kg −1 of Cd, 68.7 mg kg −1 of Ni, and 83.4 mg kg −1 of Pb [ 9 ]. Furthermore, the data of this study indicated that the mean values of the estimated heavy metals were lower than that reported by [ 40 ] for three drains (Elhoks, El-Shakhlouba and Drain 7), [ 45 ] for the Kitchener Drain, and [ 47 ] for contaminated wetlands in Egypt. In addition, Eid et al [ 48 ] recorded 11.9–12.6 mg kg −1 of Ni and 12.7–13.7 mg kg −1 of Pb in the sediment of Burullus Lake of Egypt, which tended to be lower than that estimated in this study.…”
Section: Discussioncontrasting
confidence: 74%
“…In this context, sewage sludge, synthetized fertilizers, paints, dyes, electroplating, steel industries, batteries, pipes, pesticides, soaps, antimicrobial agents, fuel combustion, etc. likely greatly contribute to the raised levels of the studied heavy metals in the studied drains of the Nile River in Egypt [ 19 , 24 , 26 , 40 , 45 ]. On the other hand, the low concentrations of Cd, Ni, and Co might suggest a probable sole natural origin.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been adapted to decontaminate polluted aquatic environments from HMs and organic pollutants (Ajiboye et al 2021) using techniques such as biochar , nano zero valent iron (Sliječpević et al 2021), and clays (Elshazly et al 2019). Other pollutants may cause serious threats to human health and ecosystems when they reach aquatic environments, including nanoparticles (Turan et al 2019;Souza et al 2021), antibiotics Xu et al 2021), microplastics (Ma et al 2020;Tang et al 2020;Pan et al 2021;Wang et al 2021), bisphenols Šauer et al 2021), retinoic acids (Yeung et al 2020), perfluoroalkylated acids (Groffen et al 2021), heavy metals (Aitta et al 2019;Karaouzas et al 2021), personal care products Lu et al 2021), antineoplastic agents (Yadav et al 2021) and COVID-19 (Kumar et al 2020a;Steffan et al 2020;Lachrich et al 2021). On the other hand, during lockdowns to combat COVID-19, the quality of surface water (Yunus et al 2020) and air (Guatam, 2020) are expected to improve.…”
Section: Aquatic Environments and Their Pollutionmentioning
confidence: 99%
“…The freshwater ecosystem includes aquatic habitats that are highly prone to pollution due to the intensive interactions between these habitats and humans (Verma, 2020). Heavy metals (HMs) are of special concern, being important inorganic pollutants that cause many problems through their toxicity as well as being non-degradable and therefore persistent in nature (Aitta et al 2019;Verma 2020). The presence of organic pollutants and pathogens can also cause major problems (Brevik et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, water bodies' contamination by HMs through discharging industrial wastewater is a worldwide environmental issue that needs to be properly addressed. Rapid industrialization has seriously contributed to the release of potentially toxic HMs to water streams (Ahmaruzzaman 2011;Reddy et al 2011;Islam et al 2016;Saha and Rahman 2018;Aitta et al, 2019;Shahedi et al 2020;Eldamaty et al, 2021). Heavy metals such as Cu, Fe, Ni, Pb, and Zn are among the most common inorganic contaminants found in industrial wastewater (Reddy et al 2011).…”
Section: Introductionmentioning
confidence: 99%